Proposta de um programa de qualidade o leite e controle da mastite em rebanho bovino de vacas holandesas - Wanderley, Guido Gomes [UNESP] (2015)
Mastitis is a disease that more burdens the world dairy sector still major obstacle to improving production. The aim of this prospective epidemiological study was to develop a mastitis control plan in a Holstein cow herd. The property has been visited for 18 months to harvest data and control plane of the institution. The first four months corresponded to the diagnostic phase, followed by an intervention phase amounting to 14 months. The control plan has reduced from 53.7% to 23.3% subclinical mastitis. The somatic cell count of the tank reduced from 1446 x 103 cells / ml to 214 x 103 cells/ml. The prevalence of clinical mastitis was 11.11% and the average incidence was 7.6%. Of the total 704 cases, 30.1% (217/704) could not be evaluated for bacteriological cure because there is no post-treatment samples, 51.3% (249/485) healed, 49.7% (236/485) failed and repeated the same pathogen or failed to isolation of a new pathogen. Of the total 485 cases that could be evaluated for bacteriological cure 71.9% (349/485), 19% (92/485), 7.4% (36/485) and 1.6% (8/485) They were, respectively, related to the first, second, third and fourth cases of clinical mastitis in the same mammary gland. There was treatment failure in 53.65% (44/82), 47.5% (165/347) and 48.21% 27/56, severity one, two and three, respectively. The mastitis control plan was effective in reducing the prevalence of subclinical mastitis and elucidate the clinical mastitis rates through simple measures of management and grounded in proper epidemiological diagnosis